Health and Economic Impact of Health Warnings and Plain Tobacco Packaging in Seven Latin American Countries: Results of a Simulation Model. Issue 11 (12th June 2020) - Alcaraz, Andrea; Hernández-Vásquez, Akram; Palacios, Alfredo; Rodríguez, Belén; Roberti, Javier; García-Martí, Sebastián; Ciapponi, Agustín; Augustovski, Federico; Bardach, Ariel; Pichon-Riviere, Andrés
Abstract: Introduction: The burden of disease attributable to tobacco use in Latin America is very high. Our objective was to evaluate the 10-year potential impact of current legislation related to cigarette packaging and warnings and expected effects of moving to a higher level of strategies implementing cigarette plain packaging on health and cost outcomes in Argentina, Bolivia, Brazil, Chile, Colombia, Mexico, and Peru, using a microsimulation model. Aims and Methods: We used a probabilistic state-transition microsimulation model, considering natural history, costs, and quality of life losses associated with main tobacco-related diseases. We followed up individuals in hypothetical cohorts and calculated health outcomes annually to obtain aggregated long-term population health outcomes and costs. We performed a literature review to estimate effects and analyzed studies and information from ministries, relevant organizations, and national surveys. We calibrated the model comparing the predicted disease-specific mortality rates with local statistics. Results: Current graphic warnings already in place in each country could avert, during 10 years, 69 369 deaths and 638 295 disease events, adding 1.2 million years of healthy life and saving USD 5.3 billion in the seven countries. If these countries implemented plain packaging strategies, additional 155 857 premature deaths and 4 133 858 events could be averted, adding 4.1 million healthy years of life and saving USD 13.6 billion in direct health care expenses of diseases attributable to smoking. Conclusions: Latin American countries should not delay the implementation of this strategy that will alleviate part of the enormous health and financial burden that tobacco poses on their economies and health care systems. Implications: Tobacco smoking is the single most preventable and premature mortality cause in the world. The Framework Convention on Tobacco Control, supported by the World Health Organization, introduced a package of evidence-based measures for tobacco control. This study adds evidence on the potential health effects and savings of implementing cigarette plain packaging in countries representing almost 80% of the Latin American population; findings are valuable resources for policy makers in the region.